Juridical Analysis of the Position of Actors "Participating in Carrying Out" in the Distribution of Illegal Drugs Based on Law Number 36 of 2009 Regarding Health (Study Decision Number 210/Pid.Sus/2023/PN Kwg) - Syahida, Nadia; Guntara, Deny; Abas, Muhamad (Journal of Law, Politic and Humanities, 2024)
The purpose of this research is to determine the regulations regarding Medeplegen's participation in Indonesian criminal law and to analyze criminal penalties for perpetrators of participation in the distribution of pharmaceutical preparations of illegal drugs. illegal in District Court Decision Karawang Number 210/Pid.Sus/2023/PN Kwg. Indonesia is a legal country that prohibits the circulation of pharmaceutical preparations or drugs forbidden without permission especially drugs the enter into the Psychotropic and Narcotics categories. But in reality, there are many distributors of pharmaceutical preparations in the form of drugs classified as psychotropics and narcotics without permits or illegally. Most of them do it not alone but in collaboration. This is included in the act of participation (Delneming), and then the party participating is called Medeplegen, as is the case in Decision Number 210/Pid.Sus/2023/PN Kwg. Qualitative and normative legal approaches are used as research methods taken from literature or material obtained from library research, and research specifications use analytical descriptive. The results of the research are: (1) That the distribution of pharmaceutical preparations with inclusions violates Article 197 of Law Number 36 of 2009 concerning Health, "taking part" or "participation" (Medeplegen) is regulated in Article 55 of the Criminal Code, and in terms of the element " inclusion” namely in the form of conscious cooperation (bewuste samenwerking). (2) There is a difference between the application of the law and the reality of the verdict in Decision Number 210/Pid.Sus/2023/PN Kwg, where the amount of the fine is less than that stated in Article 197 of the Health Law, but the author sees and appreciates the considerations The Panel of Judges and pay attention to considerations regarding mitigating circumstances for the Defendant.